Factors that Play a Role in Community Participation in Creating Healthy Alleys in Makassar City - Adhe Yuniar Batari Lipu (Journal of Public Health and Pharmacy, 2023)
This research aims to reveal the factors that play a role in community participation in creating Healthy Hallways. This research is qualitative research using a Rapid Assessment Procedures design. The informants for this research were determined using purposive sampling. The data collection technique used in-depth interviews with seven community members: 1 RT head, 1 RW head, 1 Community Health Center staff, two health cadres, and one village head. This research was analyzed using the "Content Analysis" method, then interpreted and presented in narrative and matrix form. The research results found that the factors that play the most role in community participation are the will/awareness and leadership of the local government. Thus, Community Health Center health workers responsible as health tunnel supervisors must guide the form of Communication, Information, and Education (KIE) to the community to increase community participation in the Healthy Aisle program.